Human Capital in the Innovative Economy: Manufacturing Industry - G. S. Dinzhanova; M. T. Bayetova (Экономика: стратегия и практика)
Human capital is a crucial determinator of economic development because of the rapid pace of scientific and technological progress. The objective of the research is to define the state of human capital in manufacturing and to find the link between human capital and innovation. The correlation and regression analysis of the Human Capital Index designed and calculated by World Bank and Global Innovation Index was designed and calculated by WIPO of 127 countries in the year 2020. The second part of the analysis was the human capital in the manufacturing sector. The secondary data from the Bureau of National statistics were taken from the year 1991 to the year 2020. We analyzed the composition of workers by gender composition, gender pay gap, the number of bachelors graduated of technical major, aging, and education. HCI of Kazakhstan in 2020 is dropped; a possible reason for this is the COVID-19 pandemic’s side effect on the health and education of the population. The correlation between Global Innovation Index and Human Capital Index is 0,86. The 50% gender gap is revealed in the manufacturing sector employees, which shows an upward trend. Most workers in the manufacturing industry do not have a bachelor’s degree, which means that they perform hand labor rather than mental. Probably increasing the innovation used in the country may decrease the number of employees without proper education, while the productivity of the manufacturing sector will increase. However, we should consider that unemployment will increase either.